Counselling in England Today - Hague, William (Canadian Journal of Counselling and Psychotherapy, 2012)
This article is the result of interviews with school counsellors, teachers and teachers of counsellors, as well as a review of British literature on school counselling which the author did while spending a sabbatical year in Great Britain, centered in Oxford. It has the benefits and deficits of being written "on the scene" — some familiarity with the situation but perhaps a narrowness of view from the sample one happens to take.It surveys the present status of school counselling in Great Britain, particularly the training of counsellors and finds that the British see themselves as "behind the Americans" since much of the expertise and experience comes from North America and in many ways some of the school problems that helped create the North American system of counselling are only beginning to penetrate Great Britain. Solutions for the future look rather gloomy because, despite an increase in interest in school counsellors, there are internal problems to be overcome before counselling can flourish in the schools — not the least of which are basic conservativism and economic difficulty facing the whole country.